Clinical-epidemiological profile and outcome of snakebite accidents in the State of Pará: A portrait of the last two decades - Pallaro, Eduardo Fernando; Gomes, Victor Alexandre Santos; da Rocha, Diego Matos Faria; dos Remédios Vinícius Silva; e Souza, Jeremias Jonathan de Souza; Chalkidis, Hipócrates de Menezes (Seven Editora, 2024)
Objective: The study seeks to address snakebites from venomous snakebites, focusing on the state of Pará, Brazil, over the last two decades (2003-2022). Methods: retrospective research methods were used, using data from the Notification and Notifiable Diseases System (SINAN) and the National Institute of Meteorology (INMET). Results: A total of 98,979 cases were recorded, with a predominance of men (75.5%) in the age group of 20 to 39 years (38.9%). Most cases resulted in cure (82.4%), with the brown ethnicity being most affected (78.8%). Santarém was the city with the most notifications (4,212 cases), and the snake of the genus Bothrops was the most prevalent (87.3%). Conclusion: The results highlight clinical, demographic and environmental aspects of accidents, providing insights for the efficient allocation of resources in coping with these events in Pará and for the education of the population. DOI:https://doi.org/10.56238/sevened2024.025-028